The reevaluation of the role of duodenal dysmotility in the etiopathogenesis of vesicular cholelithiasis - Viorel Moraru (The Moldovan Medical Journal, 2018)
Background: Gallstone disease and chronic calculous cholecystitis are the most prevalent gastro-enterological diseases requiring a surgical treatment. This disease occupies a special place in the pathology of the hepato-bilio-pancreatic area, which is important for the etiological diagnosis as well as for the resonance and the complex impact on the function of the adjacent organs. Besides, gallstone disease can result in serious outcomes, such as acute gallstone pancreatitis and gallbladder cancer. This article analyzes the clinico- morphological characteristics of gallbladder stones. At the same time, the role of duodenal dysmotility in the ethiopathogenesis of cholestasis was reevaluated through the contemplation of the contemporary concepts of lithogenesis. Conclusions: The pathogenesis of gallstone disease is suggested to be multifactorial and probably develops from complex interactions between many genetic and environmental factors and the state of adjacent organs. Based on its anatomical and physiological features, the duodenum is a completely unique crossroads where the digestive pathways of the stomach, liver and pancreas meet. The sealing functionality of these organs allows them to be cataloged as an integral system, and the duodenum due to its specific role exerts ”the pituitary function” of the gastrointestinal tract. Therefore, any disruption of the duodenum activity may not be etiopathogenetically reflected on the hepatobiliary-pancreatic disease, and biliary cholelithiasis is no exception in this regard. The achievement in the study of the pathophysiology of bile stones formation and the pathogenesis of gallstone disease can help to improve the complex medico-surgical treatment of this category of patients.